Eosinophils, the IL-5/IL-5Rα axis, and the biologic effects of benralizumab in severe asthma. (November 2019) - Matucci, Andrea; Maggi, Enrico; Vultaggio, Alessandra
Abstract: Bronchial asthma is a chronic inflammatory disease characterized, in a percentage of patients, as an eosinophilic inflammation of the airways. Eosinophils are recognized as a proinflammatory granulocyte playing a major role in the T2-high phenotype, which includes severe eosinophilic asthma. Eosinophilic asthma represents the majority of the phenotypic variants clinically characterized by severity and frequent exacerbations. For patients with severe uncontrolled asthma, monoclonal antibodies are used as add-on treatments. Among them, in addition to anti-immunoglobulin E therapy, biologic agents directed toward the interleukin (IL)-5/IL-5Rα axis and, thus, interfering with the pathologic functions of eosinophils, are now available. Unlike the other anti‒IL-5 monoclonal antibodies which exert an indirect effect on eosinophils, benralizumab, an afucosylated IgG1 kappa antibody directed against the α subunit of IL-5R, directly depletes eosinophils and their associated bone marrow progenitor cells through induction of antibody-dependent cell-mediated cytotoxicity, through recruitment of natural killer cells. This article reviews the role of eosinophils in the pathogenesis of bronchial asthma and discusses the potential advantageous biologic effects of benralizumab in comparison with other monoclonal antibodies targeting the IL-5 ligand. Highlights: Benralizumab displays ADCC activity on IL-5R positive cells. Benralizumab also works as an anti-IL-5 inhibitor. Benralizumab is able to highly reduce eosinophils in blood and tissues through ADCC. Benralizumab also targets eosinophil progenitors and basophils through ADCC.